Role of NGOs in motivating youths to volunteer work related to the social and economic returns in the Sultanate of Oman - Wajeha Thabit Al-Ani; Mohammed Abdulhameed Lashin; Rashid Sulaman Al Fahdi; Aisha Salim Al Harthi (Journal of Arts and Social Sciences, 2017)
This study aims to investigate the role of NGOs in motivating youths to volunteer work in the Sultanate of Oman. Also it analyzes the social and economic returns of youths’ volunteer work in civic societies and the facilities offered to them and the laws and regulations governing the work of volunteer in those societies. Qualitative approach used through collecting data from 90 interviewees represented of 85% of total population. Their responses were coded using (NVivo) program. The study result showed that there are 566 codes. Those codes were analyzed and showed that the social returns of youth volunteers provides more opportunities to them in developing their skills and socially empowering them through their participation in workshops conducted by those societies. Where the Governorate of Muscat coded higher percentage compare with the South Batinah and South Sharqiay Governorates. As for the economic returns, the results showed that it is still at low level. The study results showed there are other returns are linked to the development of society and groups related to the elderly and children. In accordance to facilities provided for youths volunteers where Dhofar governorate shows the highest percentage compared to other governorates. The study result also shows that there is a need for legislation to regulate voluntary work and preserve the rights of volunteers to ensure the continuity of youth’s participations in volunteer work. Upon the study results, many recommendations and suggestions were proposed.